2020
DOI: 10.1093/imrn/rnaa141
|View full text |Cite
|
Sign up to set email alerts
|

From Hierarchical to Relative Hyperbolicity

Abstract: We provide a simple, combinatorial criteria for a hierarchically hyperbolic space to be relatively hyperbolic by proving a new formulation of relative hyperbolicity in terms of hierarchy structures. In the case of clean hierarchically hyperbolic groups, this criteria characterizes relative hyperbolicity. We apply our criteria to graphs associated to surfaces and prove that the separating curve graph of a surface is relatively hyperbolic when the surface has zero or two punctures. We also recover a celebrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In light of Theorem A.1 in the Appendix, this property is no longer required for this paper. We keep the contents of this section in the paper nonetheless, since they have found independent interest and already been used elsewhere, e.g., [BR,HS16,Rus20], as well as in several papers in progress.…”
Section: Introductionmentioning
confidence: 99%
“…In light of Theorem A.1 in the Appendix, this property is no longer required for this paper. We keep the contents of this section in the paper nonetheless, since they have found independent interest and already been used elsewhere, e.g., [BR,HS16,Rus20], as well as in several papers in progress.…”
Section: Introductionmentioning
confidence: 99%
“…Theorem 3.2 (Special case of [21,Theorem 4.3]). Let 𝔖 be the set of witnesses for some hierarchical graph of multicurves and let 𝔗 be the set of all (not necessarily connected) subsurfaces of 𝑆 where each component is an element of 𝔖.…”
Section: The Relatively Hyperbolic Casementioning
confidence: 99%
“…Sultan showed that prefixSepfalse(S2,0false)$\operatorname{Sep}(S_{2,0})$ is also hyperbolic [24]. Previous work of the authors completed the classification, showing that prefixSepfalse(Sfalse)$\operatorname{Sep}(S)$ is hyperbolic if p3$p \geqslant 3$ or false(g,pfalse)false{false(2,0false),false(2,1false),false(1,2false)false}$(g,p) \in \lbrace (2,0),(2,1),(1,2)\rbrace$ [26], relatively hyperbolic if p=0$p =0$ and g3$g \geqslant 3$ or p=2$p=2$ and g2$g \geqslant 2$ [21], and thick of order at most 2 if p=1$p=1$ and g3$g \geqslant 3$ [22]. These results again match up with the classification in terms of witnesses given in Theorem 2.25 and employ special cases of the techniques employed here.…”
Section: Examples Of the Classificationmentioning
confidence: 99%
See 2 more Smart Citations